An Efficient Approach For Indexing Web Pages Using Page Ranking Algorithm For The Enhancement Of Web Search Engine Results - V. Pardakhe1 , Prof. R. R. Keole, Ms. Nilima , (International Journal of Scientific Research and Management (IJSRM), 2017)
As web is the largest collection of information and plenty of pages or documents are newly added and deleted on frequent basis due to the dynamic nature of the web. The information present on the web is of great need, the world is full of questions and the web is serving as the major source of gaining information about specific query made by the user. Search engines generally return a large number of pages in response to user queries. To assist the users to navigate in the result list, ranking methods are applied on the search results. Most of the ranking algorithms proposed in the literature are either link or content oriented. Proposed methodology uses, a page ranking mechanism based on frequency of keywords found in the query made by user. This approach helps to rank most valuable and relevant search results on the top of the result list. Therefore tries to enhance the search engine results.